2014
DOI: 10.1089/ars.2013.5332
|View full text |Cite
|
Sign up to set email alerts
|

The Thioredoxin Reductase-1 Inhibitor Aurothioglucose Attenuates Lung Injury and Improves Survival in a Murine Model of Acute Respiratory Distress Syndrome

Abstract: Aims: Inflammation and oxygen toxicity increase free radical production and contribute to the development of acute respiratory distress syndrome (ARDS), which is a significant cause of morbidity and mortality in intensive care patients. We have previously reported increased glutathione (GSH) levels in lung epithelial cells in vitro and attenuated adult murine hyperoxic lung injury in vivo after pharmacological thioredoxin reductase-1 (TrxR1) inhibition. Using a murine ARDS model, we tested the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 41 publications
5
36
2
Order By: Relevance
“…These results were in agreement with previous studies showing that hyperoxia leads to increased TNF-α levels in the lung [5255]. The role of cytokines in hyperoxic acute lung injury has been extensively studied [56] and other mediators such as IL-1, IL-8, IFN-γ, MIP-2 and MCP-1 play a role in this disease process.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with previous studies showing that hyperoxia leads to increased TNF-α levels in the lung [5255]. The role of cytokines in hyperoxic acute lung injury has been extensively studied [56] and other mediators such as IL-1, IL-8, IFN-γ, MIP-2 and MCP-1 play a role in this disease process.…”
Section: Discussionsupporting
confidence: 92%
“…Aurothioglucose (ATG) and auranofin (AFN) are Food and Drug Administration-approved antirheumatic drugs that potently inhibit TrxR1 (24,25). We have shown previously in vivo that ATG inhibits TrxR1, induces Nrf2-dependent gene transcription, and prevents lung injury in adult murine models (26,27). Moreover, in vitro data from our laboratory suggest that the protective effects of TrxR1 inhibition are mediated by Nrf2 activation (28).…”
mentioning
confidence: 62%
“…We have shown previously that TrxR1 disruption increases Nrf2 activation and Nrf2-mediated antioxidant responses in airway epithelial cells in vitro. TrxR1 inhibition also induces pulmonary Nrf2 activation and protection against hyperoxic and inflammatory lung injury in adult mice in vivo, suggesting the possible clinical usefulness of TrxR1 inhibitors in conditions such as acute respiratory distress syndrome (26)(27)(28). By demonstrating that TrxR1 inhibitors increase Nrf2 activation in alveolar epithelial cells in vitro and in the lungs of hyperoxia-exposed neonatal mice in vivo, the current studies extend our previous findings and support the possible clinical use of TrxR1 inhibition to prevent and/or treat BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that cellular injury in the lung is the main pathophysiological event leading to death after hyperoxia and other experimental lung injury protocols (26)(27)(28). We asked whether endothelial TLR4 protects lungs against oxidant-induced injury.…”
Section: Endothelial Tlr4 Protects the Lung Against Oxidant-induced Imentioning
confidence: 99%